Transforming subsidiaries into branches: Should we be worrying about it? - Péter Fáykiss; Gabriella Grosz; Gábor Szigel (Magyar Nemzeti Bank, 2013)
In recent years, foreign banks' presence in the form of branches instead of subsidiaries started to gain ground in most of the Central and Eastern European (CEE) countries, including Hungary. Due to the high share of foreign ownership in their banking systems, local authorities in CEE may perceive this trend towards the transformation of subsidiaries into branches as a loss of control over their financial systems. For the time being, we assess the financial stability risks related to this process to be rather moderate. First, no negative anomalies have been identified in respect of the existing branches in the Hungarian market, even though their market share is still small at this point. Furthermore, experience and our model results indicate that large universal banks, which constitute almost three quarters of the Hungarian market, are unlikely to switch to a branch model. Even though host country supervisors do not lose all responsibility for the regulation and supervision of branches, the use of certain regulatory instruments becomes more cumbersome or even impossible in certain cases. Thus, the spread of the branch model may increase the risk of contagion from parent banks in the host countries. Consequently, we think that the status quo appears to be the preferable option for the stability of the Hungarian banking system.
Keywords: G21; G28; C21; 330; branch; regulation; organisational form; microprudential supervision; macroprudential supervision